Early effects of treatment with nebivolol and quinapril on endothelial function in patients with hypertension - Korkmaz, Hasan; Karaca, Ilgin; Koc, Mustafa; Onalan, Orhan; Yilmaz, Muecahit; Bilen, Mehmet Nail (Informa Healthcare, 2008)
The objective of the present study was to compare the early effects of treatment with nebivolol and quinapril on the endothelial function in hypertensive patients. A total of 54 hypertensive patients was enrolled in the present study. One of the groups (n = 27) received quinapril 20 mg/day, and the other group (n = 27) received nebivolol 5 mg/day for a period of 4 weeks. The endothelial dysfunction was assessed using FMD (flow-mediated vasodilation) of the brachial arteries. The baseline characteristics of both groups were similar in age, gender, left venticular ejection fraction, left ventricular mass index, and body mass index. No significant difference was also found between the groups in the distribution of atherosclerotic risk factors as well as other echocardiographic, demographic, and biochemical measurements. Although the reduction of diastolic blood pressure was more pronounced in the nebivolol group after a 4-week treatment, the change in the systolic blood pressure was found to be similar in both treatment arms. Although a statistically nonsignificant increase was observed in flow-mediated vasodilation in the quinapril group (4.77% +/- 3.92%, 5.60% +/- 6.18%; p = .587), the increase in the post-treatment FMD was statistically significant in the nebivolol group (3.78% +/- 4.25%, 8.56% +/- 6.39%; p = .002). A significant change was observed in the resistive index value following flow-mediated vasodilation for both groups after treatment (p = .043; p = .027), whereas the change in the value of flow volume was significant only in the nebivolol group (p = .019).
Keywords: endothelial disfunction; hypertension; nebivolol; quinapril; FMD; resistive index